2009
DOI: 10.1016/j.chembiol.2009.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Directed Evolution and Structural Characterization of a Simvastatin Synthase

Abstract: SUMMARY Enzymes from natural product biosynthetic pathways are attractive candidates for creating tailored biocatalysts to produce semisynthetic pharmaceutical compounds. LovD is an acyltransferase that converts the inactive monacolin J acid (MJA) into the cholesterol-lowering lovastatin. LovD can also synthesize the blockbuster drug simvastatin using MJA and a synthetic α-dimethylbutyryl thioester, albeit with suboptimal properties as a biocatalyst. Here we used directed evolution to improve the properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
85
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(89 citation statements)
references
References 26 publications
1
85
0
3
Order By: Relevance
“…indeed, screening several thousand mutants is usually required to identify such improvements. 12,13 given the rather low level of Lipb activity that we observed in crude extracts, our first target for directed evolution will involve improving the overall activity of Lipb with uridine and pnPs as substrates, prior to altering the specificity toward alternative nonnatural substrates. this goal may be achieved by improving protein expression, enzyme solubility, or catalytic activity via random mutagenesis and screening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…indeed, screening several thousand mutants is usually required to identify such improvements. 12,13 given the rather low level of Lipb activity that we observed in crude extracts, our first target for directed evolution will involve improving the overall activity of Lipb with uridine and pnPs as substrates, prior to altering the specificity toward alternative nonnatural substrates. this goal may be achieved by improving protein expression, enzyme solubility, or catalytic activity via random mutagenesis and screening.…”
Section: Discussionmentioning
confidence: 99%
“…12 in another example, an agar-based diffusion assay was used to improve the activity of the acyltransferase Lovd for the semisynthesis of simvastitin by directed evolution. 13 in addition, a well-established Hts for cytochrome P450s was harnessed to identify variants for the regioselective deprotection of monosaccharide substrates.…”
mentioning
confidence: 99%
“…Both adopt the a/b-hydrolase fold. [14] A few esterases and acyltransferases adopt other folds such as the b-lactamase fold adopted by esterase B from Burkholderia gladioli [15] and simvastatin acyltransferase, [16] but these other folds are not considered in this paper. Both esterases/lipases and acyltransferases in the a/ b-hydrolase-fold class contain a Ser-His-Asp(Glu) catalytic triad, an oxyanion hole and follow a ping-pong bi-bi reaction mechanism involving an acyl-serine enzyme intermediate.…”
Section: Introductionmentioning
confidence: 99%
“…Crystallization revealed that mutated residues were scattered on the tertiary structure, distant from the active site and in both solvent-exposed and buried regions. These residues, like most residues identified using directed evolution, would have been difficult to identify using the crystal structure alone [127].…”
Section: Directed Evolutionmentioning
confidence: 99%